2005
DOI: 10.1007/s00134-005-2801-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluid balance and weaning outcomes

Abstract: These data suggest that fluid balance, a potentially modifiable factor, is associated with weaning outcomes. A randomized study is required to determine whether diuresis to treat positive fluid balance expedites liberation from mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 15 publications
6
100
0
8
Order By: Relevance
“…Previous observational studies [8][9][10] on weaning procedures found a correlation between higher fluid balance and extubation failure. However, there was considerable diversity in terms of populations evaluated, weaning and extubation protocols, and outcomes analyzed.…”
Section: See the Related Editorial On Page 1213mentioning
confidence: 99%
“…Previous observational studies [8][9][10] on weaning procedures found a correlation between higher fluid balance and extubation failure. However, there was considerable diversity in terms of populations evaluated, weaning and extubation protocols, and outcomes analyzed.…”
Section: See the Related Editorial On Page 1213mentioning
confidence: 99%
“…The SBT is presently the major diagnostic tool to determine if patients can be successfully extubated [1], and recent recommendations have been made to further increase the likelihood of successful extubation [8][9][10][11][12][13][14][15]. Nonetheless, extubation failure-defined as the need for ventilatory support or death within 48 h following extubation (adapted from [1])-is still prevalent, with reported reintubation rates of up to 19% [1,16,17] and 5-24% for rescue therapy with non-invasive ventilation (NIV) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The recommended approaches to evaluate the likelihood of successful extubation rely on objective criteria assessed by the clinician [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Little emphasis has been placed so far on the patients' subjective evaluation of the potential to sustain autonomous breathing, which might be influenced by psychological factors as well as the perceived work of breathing.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, a few interesting studies have been published on weaning and fluid balance. In one observational study, Upadya et al 6 found a correlation between negative fluid balance in the 24 h before an SBT and extubation success, suggesting that approaching weaning with a positive balance might be detrimental. Similarly, in a large multicenter observational study, Frutos-Vivar et al 7 reported that one of the risk factors for re-intubation was a positive fluid balance in the 24 h before extubation.…”
Section: See the Original Study On Pages 1091 1097mentioning
confidence: 99%